Reduction of morbidity in hepatosplenic Schistosomiasis mansoni after treatment with praziquantel: a long term study - Ana Lúcia C. Domingues; Amaury D. Coutinho (Sociedade Brasileira de Medicina Tropical (SBMT), 1990)
Forty-two with hepatosplenic patients treated with praziquantel and followed up for 5 years. One half of the patients received a single 30 mg/kg dose and the other half, two doses of 25 mg/kg given 4 hrs apart. According to Hoffman and Kato-Katz stool exams, an 83.3% cure rate, was observed after twelve months. Stool egg counts in cases of incomplete cure were greatly reduced. Liver function, as assessed by serum levels of aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase and alkaline phosphatase activities as well as albumin and gamma globulin showed marked improvement after one year. Hepatomegaly was reduced in 81.0% of patients and splenomegaly in 78.8%. Spleen regression was complete in 15.1% of the total, and in 18.5% of those with compensated hepatosplenic disease. As a result of these observations, the authors recomend early treatment with anti-schistosomal medication, either oxamniquine or praziquantel, to halt progression of disease and reduce splenomegaly. Quarenta e dois pacientes esquistossomóticos hepatosplênícos, tratados com praziquantel, foram acompanhados por cinco anos. Metade dos pacientes recebeu uma dose simples de 30mg/kg; a outra metade, recebeu duas doses de 25mg/kg dadas com intervalos de 4 horas. A taxa de cura, de acordo com os exames de fezes pelos métodos de Hoffman cols e de Kato-Katz, durante 12 meses foi de 83,3%. Nos casos com cura incompleta, os ovos contados nas fezes foram muito reduzidos. A função hepática, estimada pelo nível, no soro, de aspartato aminotransferase,, alamina aminotransferase, gama glutamiltransferase e fosfatase alcalina bem como, de albumina e gama globulina mostrou acentuada melhora após um ano. Hepatomegalia foi reduzida em 81,0% dos pacientes e esplenomegalia em 78,8%. A regressão do baço foi completa em 15,1% do total e em 18,5% daqueles com forma hepatosplênica compensada. Como resultado destas observações, os autores recomendam tratamento precoce com medicação antiesquistossomótica com oxamniquine ou praziquantel para ...